2018
DOI: 10.1097/pts.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

A Transactional “Second-Victim” Model—Experiences of Affected Healthcare Professionals in Acute-Somatic Inpatient Settings: A Qualitative Metasynthesis

Abstract: and transparent account of the study being reported; that no important aspects of the study have been omitted; and that any discrepancies from the study as planned (and, if relevant, registered) have been explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 62 publications
(757 reference statements)
0
43
0
Order By: Relevance
“…For example, it is possible that respondents met the criteria for probable PTSD but were coping with different underlying mental health problems, resulting in more respondents meeting the threshold criteria for traumatic stress. It should also be considered that the survey was unable to reach midwives who have retired or have left the profession, given that one of the outcomes reported by health care workers who experience trauma is changing their position or leaving the profession . Nor was the study able to reach midwives who were not members of KNOV.…”
Section: Discussionmentioning
confidence: 96%
“…For example, it is possible that respondents met the criteria for probable PTSD but were coping with different underlying mental health problems, resulting in more respondents meeting the threshold criteria for traumatic stress. It should also be considered that the survey was unable to reach midwives who have retired or have left the profession, given that one of the outcomes reported by health care workers who experience trauma is changing their position or leaving the profession . Nor was the study able to reach midwives who were not members of KNOV.…”
Section: Discussionmentioning
confidence: 96%
“…13 The need for trained professionals within institutions to identify individuals who are at risk for becoming a second victim was emphasized in the literature. 13,14 The two types of indicators reported that can be used to assist in identification of a second victim include psychosocial and physical symptomatology. Examples of psychosocial symptoms include stress, anxiety, depression, worry, shame, inadequacy, difficulty concentrating, and guilt.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of psychosocial symptoms include stress, anxiety, depression, worry, shame, inadequacy, difficulty concentrating, and guilt. 4,9,14,15 Physical symptoms may include increased heart rate, elevated blood pressure, anorexia, fatigue, muscle tension, and increased respiratory rate. 3,15 Literature on the current management of the second victim phenomenon is advancing knowledge on the subject; however, it is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations